For new 2008 add maths syllabus students
This question combines the modulus function with integration.
Perhaps you will like to solve it.
Question
Integrate l x^2 + 2x -3 l dx from x = 0 to x = 2
[The sign in blue is the modulus sign]
Thank you for your kind attention.
Regards,
ahm97sic
I don't know what to do with the modulus function ):
I only know that if I integrate x^2 + 2x -3 dx I will get (if there's no careless mistake) x^3/3 + x^2 - 3x + c
>< Care to enlighten?
I think I would do this:
x^2 + 2x - 3 = (x-1)(x+3)
Square it, and the modulus is gone.
so integrate (x-1)^2(x+3)^2
integrate x^4+4x^3-2x^2-12x+9
= x^5/5 + x^4 - 2/3x^3 - 6x^2 + 9x + c
Any mistakes/misconceptions?
Hopefully this doesn't come out in the exam.
EDIT: I made a mistake, can't pinpoint, but I cannot just square an equation without warning. I shall wait for some directions for corrections
How can you just square it? I think the direction to square it is correct. But, i would do this:
Square root (integrate square of the function)
or integrate (square root(square of the function))
kinda literal dont you think? XD
pple... dun do till so troublesome...
first, you must note which part is positive and which is negative... A simple method is to do a quick sketch of the graph.
For e.g., x² + 2x - 3 = (x-1)(x+3)
The roots are -3 and 1, and since it is a U shaped curve, anything where x is such that -3 < x < 1 is smaller than zero
For integrating from x = 2 to x =0, it is the same as the negative of integrating from x = 0 to x = 2
Note that for x between 0 and 1, x² + 2x - 3 is negative
for x between 1 and 2, x² + 2x - 3 is positive
So,
integrate |x² + 2x - 3| from x = 2 to x = 0
= - integrate |x² + 2x - 3| from x =0 to x = 2
= - [integrate -(x² + 2x - 3) from x = 0 to x = 1 + integrate x² + 2x - 3 from x =1 to x = 2]
============> add a negative sign for 0<x<1 because the mod sign flipped it from negative to positive; a minus sign does the same thing for the negative portion
= - [ (-x³/3 - x² + 3x) from x = 0 to x =1 + x³/3 + x² - 3x from x = 1 to x = 2]
= - [ (1.667 - 0 ) + (0.667 - (-1.667))]
= -4
Regards,
Eagle
(ExamWorld)
Edit: Just realised it was Ahm97sic who posted out the question for everyone :D
But nvm... Already answered... Good question though :D
So, it's like you're totally ignoring the modulus sign? Since modulus reflected the graph to positive shouldn't your area be positive too?
Originally posted by Garrick_3658:So, it's like you're totally ignoring the modulus sign? Since modulus reflected the graph to positive shouldn't your area be positive too?
that's because the integration is from 2 to 0, not 0 to 2
Mind doing some further explanations between integration and modulus? I still don't get it.
Hi Garrick_3658, iamapebble and Davidche
Question
Integrate l x^2 + 2x -3 l dx from x = 0 to x = 2
[The sign in blue is the modulus sign]
Answer
Step 1 : Sketch the curve y = x^2 + 2x -3
The curve will be an "U-shaped" curve.
The curve will cut the x-axis at x = 1 and x = - 3
Part of the curve will be below the x-axis.
Step 2 : Sketch the curve y = l x^2 + 2x - 3 l
Part of the curve that is previously below the x-axis will be reflected to be above the x-axis.
It will be observed that the area from x = 1 to x = 2 is positive.
The area from x = 0 to x = 1 will be positive too but it will be difficult to integrate to find this area using the modulus function, so instead we will integrate the curve y = x^2 + 2x - 3 that is below the x-axis from x = 0 to x = 1. These two areas are the same as these areas are the reflection of one another.
Step 3 : Find the area
Integrate l x^2 + 2x -3 l dx from x = 0 to x = 2
= Integrate x^2 + 2x -3 dx from x = 1 to x = 2
+ Integrate [- ( x^2 + 2x -3)] dx from x = 0 to x = 1
= 4
So, you have learnt the trick of solving this type of question. So, now you know how to solve it if this type of question comes out in the "O" level add maths exam.
Thank you for your kind attention.
Regards,
ahm97sic
ahm97sic, from your answer, I think you should phrase it as integrating from x = 0 to x = 2
Not the other way round :D
Entry is deleted.
hi ahm97sic
the terminology is incorrect
means a and b are the lower limit and upper limit of the integration
It means integrating from x = a to x = b
This is because
Going the other way round, you will have to put a negative sign.
Integrating from x = 2 to x = 0 is equal to the negative of integrating from x = 0 to x = 2
Hi Eagle,
Yes, the terminology that I used in the question is incorrect.
It should be to integrate from x = 0 to x = 2.
I will make the changes to the question now.
Regards.
ahm97sic.
Ohhhh I just saw the question requres x = 0 to x = 2, no wonder I was thinking why everyone do so long steps, hehe. Anyway, thanks! I get it now! :D
eagle has sharp eyes.
Eagle don't wear spectacles ok.
ohh i'm worried about my amaths alr.. i dont seems to be able to make it for this type of questions in Os.